CCR2 Inhibition Reduces Neurotoxic Microglia Activation Phenotype After Japanese Encephalitis Viral Infection - Singh, Swati; Singh, Gajendra; Tiwari, Swasti; Kumar, Alok (Frontiers in Cellular Neuroscience, 2020)
Controlling of pro-inflammatory response of microglia by targeting chemokines (C-C motif) receptor 2 (CCR2) could be important therapeutic approach for Japanese encephalitis virus (JEV) infection. Here, through JEV infection to BV2 microglia and young BALB/c mice, we investigated that CCR2 is highly up-regulated after JEV infection and plays key role in determining microglia activation phenotype and associated with neurotoxic proinflammatory mediators of TNF-α and IFNγ. In addition we found JEV infection to BV2 microglia causes increase in microglia proliferation and cell body area at day 1 and day 3. CCR2 inhibition, by using its antagonist molecule; RS102895, significantly reduces microglia reactive phenotype and nitric oxide production. Further, to define the role of CCR2 in functional response of microglia and their activation phenotype, we performed in vitro cell scratch functional assay and image J analysis. When compared to control, microglia cells showed significant increase in elongated or rod like activated phenotype in JEV infected cells at 24 h post-infection and CCR2 inhibition significantly reduced the elongated activation phenotype induced by JEV infection, suggesting that CCR2 acts as a critical regulator for microglia activation phenotype after JEV infection. We found that JEV infected mice treated with RS102895 had less microglia activation and reduced mRNA expression of CCR2 and proinflammatory mediators such as IFN-γ in cortical tissue. Collectively, our data indicates that CCR2 drives reactive phenotype of microglia and its inhibition reduces microglia activation and neurotoxic pro-inflammatory mediators following JEV infection.